GOSCAN / Muhammad Auji Sufi Mohamad Sauffi ... [et al.] - Mohamad Sauffi, Muhammad Auji Sufi; Ramli, Muhammad Akmal Anwar; Ajini, Muhammad Taufiq Ridzwan; Nor Azmi, Muhammad Ariff Danial; Shamsul Baharin, Muhammad Nyzrien Sheqal; Hamid, Faizal; Mohd Hafiz, Siti Humaira Aqwa (2022)
Fingerprint scanners are unique and highly secure, they are used to lock/unlock devices and apps without having to remember passwords, easier, cheaper and faster setup, online transactions. line becomes more convenient when you press the screen with your finger, fraction of a second. The fingerprint scanner offers very high accuracy, it is the most economical biometric authentication technique for PC users, it is one of the most developed biometrics and the small storage space required for the sample biometrics helps to reduce the required database memory size. The fingerprint scanner scans & saves fingerprints, it is used to open the door or power on the device, it is limited by the quality of the technology used in its construction, many laptops have been released with these devices on board to control machine access by hackers or other criminals, or simply as a security device. Fingerprint biometric reader is that it is quite easy to copy the key or write an alarm code and pass it on to unauthorized people, it is almost impossible to copy someone else's fingerprint in a form that is not visible. The scanner will recognize it. Other types of access control solutions have a weakness that they depend on something that can easily be lost, shared, or duplicated. Fingerprints have none of these weaknesses, anyone with an approved fingerprint doesn't necessarily have access to another part of the security system. Hackers are experts at finding your computer password, they may not have a usable copy of your fingerprint, fingerprint scanner provides extra security, human fingerprint contains unique zigzags and crests that the average scammer can hardly duplicate. Fingerprint scanners can scan for suspicious possibilities or verify identity remotely, instead of requiring individuals to return to the station or waste time processing ink fingerprint cards.